The utility of positron emission tomography/computed tomography in target delineation for stereotactic body radiotherapy for liver metastasis from primary gastric cancer: an illustrative case report and literature review - Lewis, Gary D.; Chiang, Stephen B.; Butler, E. Brian; Teh, Bin S. (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
The liver is a common site for metastatic disease for many cancers. Radiation therapy is one means of treatment for liver metastases, especially for patients unable to undergo surgery or ineligible for systemic chemotherapy. In particular, stereotactic body radiotherapy (SBRT) has become an important option in the treatment of metastatic disease in the liver. SBRT delivers ablative doses of radiation in relatively few fractions. As such, precise and clear imaging plays an important role in maximizing disease control while minimizing normal tissue toxicity. We present a case that highlights the importance of using multiple imaging modalities for target volume delineation in stereotactic radiation treatment of liver metastases.